Habituation in Frankliniella occidentalis to deterrent plant compounds and their blends. Issue 3 (22nd April 2014) - Egger, Barbara; Spangl, Bernhard; Koschier, Elisabeth Helene
Abstract Feeding and oviposition deterrence of three secondary plant compounds and their 1:1 blends to adult female Frankliniella occidentalis Pergande (Thysanoptera: Thripidae) and the potential for habituation of the thrips to the pure compounds and the 1:1 blends at various concentrations were investigated. In choice assays, we tested dose‐dependent feeding and oviposition deterrence of the two fatty acid derivatives methyl jasmonate and cis‐jasmone, the phenylpropanoid allylanisole, and their blends when directly applied to bean leaf discs. The concentration required to reduce the feeding damage by 50% relative to the control treatment (FDC50) was lowest for cis‐jasmone and highest for allylanisole. The feeding deterrent effect of both jasmonates was increased when blended with allylanisole. Feeding deterrence and oviposition deterrence were strongly correlated. In no‐choice assays conducted over four consecutive days, we discovered that dilutions at low concentrations (FDC15) applied to bean leaves resulted in habituation to the deterrents, whereas no habituation occurred at higher concentrations (FDC50). We observed a tendency that the 1:1 blends reduce the probability that thrips habituate to the deterrent compounds. Our results may be useful in the development of integrated crop protection strategies with the implementation of allelochemicals as pest behaviour‐modifying agents.